All Days 2015
DOI: 10.2118/176533-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Cross Link Polymer Sealant for Curing Severe Lost Circulation Events in Fractured Limestone Formations

Abstract: Preventing and curing fluid losses in limestone formations is one of the most challenging loss situations to prevent and control. Loss zones are unpredictable, due to large vugular zones and extended and connected fracture structures. Often these limestone intervals are depleted reservoirs. Typically, calcium carbonate pills containing various size distributions are part of the lost circulation armory in reservoir sections. However, results are highly variable and not suitable for large-scale losses. This is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The pill is formulated by synthetic water‐soluble polymers and metal crosslinkers in monovalent high‐density brine. A crosslinked polymer sealant is successfully applied for curing severe loss circulation while drilling in Kuwait across fractured limestone formations . Ziad et al reported the first successful reservoir isolation using exclusively a temporary gel plug that allowed safe and successful execution of a mechanical descaling operation without using CaCO 3 chips for well workover in high‐temperature/high‐pressure gas wells in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…The pill is formulated by synthetic water‐soluble polymers and metal crosslinkers in monovalent high‐density brine. A crosslinked polymer sealant is successfully applied for curing severe loss circulation while drilling in Kuwait across fractured limestone formations . Ziad et al reported the first successful reservoir isolation using exclusively a temporary gel plug that allowed safe and successful execution of a mechanical descaling operation without using CaCO 3 chips for well workover in high‐temperature/high‐pressure gas wells in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%